The Implementation of Ankiapp to Improve Students’ Vocabulary Mastery - Mujahidah; Hasanah, Nurul; Yusuf, Muh.; Zulfah; Fatmasyamsinar, Andi Asti (Association of Language Teachers in Southeast Asia (ALTSA), 2024)
This study aims to investigate the potential enhancement of students' vocabulary mastery through the utilization of AnkiApp. The research design employed in this study is a pre-experimental design. The population under scrutiny comprises 48 students distributed across three classes. The sample selected for this study is Class VII.1, consisting of 15 students, chosen through purposive sampling techniques. The research procedure involves the initial administration of a pre-test to assess the baseline vocabulary mastery of the students before the implementation of the AnkiApp intervention. Subsequently, a post-test is administered to evaluate the impact of AnkiApp on vocabulary learning. Data analysis is conducted through automated procedures utilizing Microsoft Excel 365, employing the paired two-sample t-test from the toolbar menu to compare the average scores. The findings reveal that the mean score of the students' post-test is 68.4, surpassing the average score of the students' pre-test, which stands at 26.6. This discrepancy indicates a statistically significant improvement in students' vocabulary mastery resulting from the effective implementation of AnkiApp.